PENGEMBANGAN MEDIA PEMBELAJARAN POWTOON TERINTEGRASI NILAI-NILAI KEISLAMAN KELAS X MAN 1 METRO - Yuni Arsih Indah Lestari; Tiara Anggia Dewi (PROMOSI: Jurnal Program Studi Pendidikan Ekonomi, 2020)
The lack of using various media in instructions causes students to feel bored. While the lack of use of facilities and infrastructure such as LCD to assist the learning process will be less effective. The material and media used in MAN 1 Metro have not yet integrated Islamic values while the scope of the school is Madrasah. We need learning media that is under the background of the Madrasah/ Islamic school, which is based on Islamic values. The purpose of this research is to produce a Powtoon animation video integrated with Islamic values that is valid and practical.The development model used is a 4D model which consists of 4 stages (Define, Design, Development, and Dissemination). The results show that the Powtoon instructional media integrated with Islamic values are valid for use in the instructional process. The results of the validation by media experts with a percentage of 87% is categorized as very strong criteria, the material experts categorized a very strong rate of 85%, and religion experts scored a very strong percentage with 96%. The results of trials of integrated Powtoon animation video integrated with Islamic values to students with a percentage of 95% are very strong. This condition shows that the Powtoon instructional media can be used as an instructional media. Based on the recapitulation, it can be concluded that the Powtoon animation video integrated with Islamic values is a valid and practical instructional media in the instructional process.Keywords: Development, Instructional Media, Powtoon Integrated with  Islamic Values